An Industrial systems design study on Universe Cybercafe - Garcia, Paolo; Gutano, Georgina; Lim, Angelito; Pereyra, Janice (Diliman, Quezon City College of Engineering, 2003)
An Industrial Systems Design Study was conducted on Universe Cybercafe in all its eleven branches. The group documented the existing system and studied the overall structure of the company and all other aspects that contribute to the services they offer. The documentation of the existing system was accomplished through interviews with the branch managers and staffs and actual observations. The group studied the company's corporate strategy, marketing and service strategies, the Standard Operating Procedure, the presentation and layout, the inventory management and the waste management of the branches. The group then identified the company's strengths, weaknesses, opportunities and threats through a SWOT analysis. After documenting the existing systems, major areas of concern were identified taking into account the problems perceived by the personnel and those perceived by the group. An Ishikawa diagram was constructed to summarize the identified problems. The two major areas of concern identified were declining market share and inefficient employees. The declining market share was further justified by data from National Statistics Office and a survey conducted by the group. After identifying the problems of the company, a TOWS matrix was constructed to come up with initial recommendations. After creating alternatives for the different problems, the optimal solutions were determined. The final recommendations of the group are as follows: hire at least one area manager, purchase new computers, subscribe to a different server, transfer the excess units from SM Pampanga to other branches that has queuing or sell the excess units and purchase webcams, implement polo and slacks uniform, relocate UCafe Megamall, advertise, revise training procedures, create concrete job qualifications/specifications, redesign, schedule general cleaning, purchase kitchen utilities and provide restroom facility in Park Square 1.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Universe Cafe; Internet access services; System design